Perancangan Sistem Informasi Peminjaman dan Pengembalian Rekam Medis Rawat Jalan di Rumah Sakit Muhammadiyah Bandung - Israwati; Sali Setiatin; Falaah Abdussalaam (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2021)
This research was conducted based on the problem of managing the borrowing and returning outpatient medical records at the Muhammadiyah Hospital Bandung which aims to find solutions to these problems to support the effectiveness of medical record services. The research method used in this research is a qualitative method with a descriptive approach. The data collection techniques used were interviews, observation, and study approach. In making the software design the writer uses the waterfall method and the supporting applications used are Microsoft Visual Studio 2010 and Microsoft Access 2013. From the results of the research conducted, the authors found several problems in the management of borrowing and returning outpatient medical records, namely: (1). There were no medical records found on the storage shelf; (2). Recording of borrowing and returning medical records still uses a manual system; (3). The absence of reports on borrowing and returning medical records. The suggestions that can be given by the author, namely : (1). It is better if the borrowing of medical records is determined by the due date so that there are no more medical records that are late to be returned to the storage room; (2). An information system is needed on borrowing and returning medical records to support activities in the hospital, especially in making reports on borrowing and returning medical records. The result of this research is an information system for borrowing and returning medical record files at Muhammadiyah Hospital Bandung.